Multi criteria tacit knowledge acquisition framework (MC-TKAF) using fuzzy delphi method for supporting talent development intervention program in Malaysian higher education institution - Yau’mee Hayati, Hj Mohamed Yusof; Ruzaini, Abdullah Arshah; Awanis, Romli (IOP Publishing, 2020)
There are certain qualities and traits needed to be qualified as Academic Leader or Academic Manager. However, there is a lack of study regarding the preparation to develop and prevent the loss of these qualities and traits among the talented academicians. Lacking of this preparation will also lead to certain Academic Leadership Management roles leave vacant without being occupied. Thus, there is a requirement to have an appropriate model to measure the knowledge, skill and experience among potential academicians during Talent Development Intervention program. This paper aims to form criteria based proposed multi criteria tacit knowledge acquisition framework using fuzzy Delphi method in phase 2 of the study. Ten (10) expertise were used to form consensus finding. Result show that elements that are evaluated by the experts with rate of consensus between 50% to 90%. This finding will enable the proposed model to be evaluated using analysis software for model fitness towards tacit knowledge competence of potential Academic Leader or Academic Manager.